Use Of The Monopoly Game As A Media For Learning Mathematics The Main Discussion Of Space Building: The Utilization Of The Monopoly Game As A Mathematical Learning Media Subject Geometry Shape - Komarullah, Hafif (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2024)
Mathematics is a comprehensive and general field, which has a very vital contribution to various fields of science and the development of human thought patterns, as well as underlying the growth of modern technology. Mathematics is taught at various levels of education from elementary school to university level. One of the materials taught in elementary school is building space. There are many geometric shapes discussed in elementary school mathematics material, namely cubes, blocks, prisms, pyramids, cones, cylinders and balls. A geometric shape is defined as a shape that has length, width and height. Building space is one of the materials that is considered difficult for students to understand. This is because students are not careful in distinguishing variables in spatial shapes. Apart from that, monotonous learning methods cause students to be less interested in studying volume material. Therefore, researchers want to apply a learning method using modified monopoly game media. Monopoly game is one of the most famous board games in the world. The goal of this monopoly game is to control all the tiles on the board through buying, renting, and exchanging properties in a simplified economic system. Researchers will use the monopoly method to find the volume and surface area of geometric figures, so that students will be interested in trying to do it. Researchers provide questions and prizes in the game. Apart from playing while learning using this monopoly method, students can more easily memorize the formulas for finding the volume of geometric figures. The population of this research is class 5 at SDN Sukamakmur 01. The sample used in this research is 30 class 5 students from SDN Sukamakmur 01 who will be divided into experimental class and control class. The expected result of this research is that students can better understand and be able to work on the questions that have been given related to spatial shapes.